KEANEKARAGAMAN TINGKAT POHON PADA HUTAN ADAT PENGAJID DESA SAHAN KABUPATEN BENGKAYANG - Tambunan, Helmut; Manurung, Togar Fernando; Ardian, Hafiz (Universitas Tanjungpura, 2018)
The forest is an area that is overgrown with thick trees and other plants. A collection of trees is conidered forest if it is able to create a microclimate and unique and different environmental conditions than other regions. Customary forests are state forests that are within the territory of indigenous forest peoples. All forms of business and uses that use customary forest must certainly pay attention to the environment and its conservation efforts. Species diversity is a measure that states the variation of plant species from a community that is influenced by the number of species and relative abudance of each species. The study aimed to determine the diversity of the tree level in the traditional forest of the Sahan instructors of Bengkayang Regency. The research method is field survey using a striped line which is a combination of path and plot methods. The results showed that 93 species were classified as 38 families. The species composition is dominated by the type of Dryobalanops oblingifolia, Shorea leavis, Shorea parfifolia and Syzygium antisepticum. The type that has the highest INP value is Dryobalanops oblingifolia, Syzygium antisepticum, Shorea parfifolia, Shorea ovalis, Syzygium grande and Dryobalanops leavis. The dominance index has a value (0,12) which shows low dominance. The species diversity index has a value (1,61) belonging to the medium class. The species abudance index shows an almost even growth rate of trees which is indicated by the value (e) approaching (1) which is 0,81.Keywords: community forest, diversity, forests.